Tyrosine Kinase Inhibitor discontinuation in Chronic Myeloid Leukemia: eligibility criteria and predictors of success. Issue 8 (12th April 2022) - Inzoli, Elena; Aroldi, Andrea; Piazza, Rocco; Gambacorti‐Passerini, Carlo
Abstract: TKI discontinuation proved to be safe and feasible in patients with CML with deep and durable molecular responses, introducing an additional treatment goal for these patients beyond overall survival. However, treatment interruption is a safe procedure only with appropriate patient selection and monitoring. Clinical and biological factors associated with better outcomes do not yet offer a precise stratification of patients according to their risk of relapse. This article aims at reviewing the leading studies present in the field in order to define eligibility criteria for discontinuation and predictors of success.